2021
DOI: 10.3390/sym13030426
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cairo Metro Tunnel Excavation on Pile Deep Foundation of the Adjacent Underground Structures: Numerical Study

Abstract: Day by day the call to solve traffic congestion problems is increasing. Subway tunnels and high-speed railway are commonly used for transportation. Therefore, tunnel construction induces soil movement, which in turn affects the stability and integrity of adjacent existing buildings. A series of numerical simulations have been established to investigate the effects of tunnel construction of the Greater Cairo Metro–Line 3-Phase-1 on adjacent pile cap foundations of Garage El-Attaba building. Many parameters have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…It can be observed in the Figure 11 that the settlement of the pile remained constant and only to occur minimal increment throughout the tunnelling progression as the settlement only gained 0.04% while 1.5D gained 0.02%. These findings indicate a good agreement with the recent studies of Ayasrah et al [32] that have shown that an inducement of pile head settlement fades as the distance between the pile and the tunnel axis is twice the tunnel diameter. However, these behaviours are much differ from Sohaie's result which can be compared to 1D and 2D that experience an increment in their settlement gradually and began rapidly drop from -0.5D from the tunnel face.…”
Section: Pile Induced By Tunnelingsupporting
confidence: 93%
See 1 more Smart Citation
“…It can be observed in the Figure 11 that the settlement of the pile remained constant and only to occur minimal increment throughout the tunnelling progression as the settlement only gained 0.04% while 1.5D gained 0.02%. These findings indicate a good agreement with the recent studies of Ayasrah et al [32] that have shown that an inducement of pile head settlement fades as the distance between the pile and the tunnel axis is twice the tunnel diameter. However, these behaviours are much differ from Sohaie's result which can be compared to 1D and 2D that experience an increment in their settlement gradually and began rapidly drop from -0.5D from the tunnel face.…”
Section: Pile Induced By Tunnelingsupporting
confidence: 93%
“…It can be observed in Figure 13 the pile with 1D distance have developed an axial compressive force as the magnitude increases to the tip of the pile as large portion of the pile are in Zone B. Meanwhile the pile with 2D distance developed a similar trend with the pile with 1D but developed an axial tensile force with a small portion of axial compressive force as small portion of the upper pile are placed in Zone B. Ayasrah [32] stated that the middle and the lower part of the pile have significant effect by the axial force during tunnel excavation. Thus, the findings are in good agreement with Jongpradist [9] and Selemetas [26] zone of influence.…”
Section: Pile Axial Forcementioning
confidence: 85%
“…Taiyari et al studied the efficiency of various meta-heuristic optimization algorithms in the optimization design of the pile wall's retaining system [7]. Ayasrah et al studied the influence of tunnel construction on adjacent pile foundation by numerical simulation [8]. Iwasaki et al obtained the pile ultimate load capacity and creep load characteristics, based on full-scale short and long-term load tests [9].…”
Section: Previous Researchmentioning
confidence: 99%
“…The maximum ground settlement decreases with the decrease of tunnel diameter, and increases with the decrease of tunnel spacing, and the influence of tunnel diameter on the maximum ground settlement is much greater than that of tunnel spacing. Given the relevant research, Ayasrah et al (2021) have studied the influence of tunnel diameter, buried depth and other parameters on the adjacent construction of Greater Cairo Metro-Line 3-Phase-1. It is found that the axial settlement of pile decreases with the decrease of tunnel diameter, which is consistent to the conclusions of this paper.…”
Section: Surface Settlement Affected By Tunnel Diametermentioning
confidence: 99%